Characterization of Interplay Between Autophagy and Ferroptosis and Their Synergistical Roles on Manipulating Immunological Tumor Microenvironment in Squamous Cell Carcinomas - Chen, Lijie; Niu, Xing; Qiao, Xue; Liu, Sai; Ma, Hongmei; Shi, Xueqing; He, Xuemei; Zhong, Ming (Frontiers in Immunology, 2022)
Objective: Squamous cell carcinomas (SCCs) with shared etiology, histological characteristics, and certain risk factors represent the most common solid cancers. This study reports the crosstalk between autophagy and ferroptosis at the molecular level in SCCs, and their roles on the immunological tumor microenvironment (TME) of SCCs. Methods: In this study, the connections between autophagy and ferroptosis were characterized in SCCs by analyzing the associations between autophagy- and ferroptosis-related genes in mRNA expression and prognosis, protein-protein interactions and shared signaling pathways. Autophagy potential index (API) and ferroptosis potential index (FPI) of each tumor were quantified for reflecting autophagy and ferroptosis levels via principal-component analysis algorithm. Their synergistical roles on TME, immunity, drug resistance and survival were systematically analyzed in SCCs. Results: There were close connections between autophagy and ferroptosis at the mRNA and protein levels and prognosis. Both shared cancer-related pathways. The API and FPI were separately developed based on prognostic autophagy- and ferroptosis-related genes. A high correlation between API and FPI was found in SCCs. Their interplay was distinctly associated with favorable prognosis, enhanced sensitivity to chemotherapy drugs (Sunitinib, Gefitinib, Vinblastine and Vorinostat), an inflamed TME and higher likelihood of response to immunotherapy in SCCs. Conclusion: This study is the first to provide a comprehensive analysis of the interplay between autophagy and ferroptosis and their synergistical roles on manipulating the immunological TME in SCCs. These findings indicated that the induction of autophagy and ferroptosis combined with immunotherapy might produce synergistically enhanced anti-SCCs activity.